Patient satisfaction and an international dental graduate workforce programme. Issue 3 (12th April 2018) - Skapetis, Tony; Ajwani, Shilpi; Bhole, Sameer
Abstract : Purpose: The New South Wales International Dental Graduate (N-IDG) programme was an Australian state government workforce initiative to support rural public dental services. The purpose of this paper is to evaluate patient satisfaction following dental treatment provided by an IDG workforce. Design/methodology/approach: This cross-sectional descriptive study used a validated questionnaire survey instrument to measure patient satisfaction ( n =813) following treatment provided by IDGs enroled in the N-IDG programme, compared to their mentors. Domains included dentists' professional competency, personality and the dental surgery organisation. Analysis of closed and open question responses was performed using domain grouping, frequency and χ 2 analysis. Findings: Patient satisfaction across the IDG and mentor workforce was similar and very positively skewed with differences detected across perceived treatment quality ( p =0.03), clinician efficiency ( p =0.05) and answering of questions ( p =0.05). These results favoured treatment provided by IDGs over mentors. This study demonstrated few differences between IDGs under limited registration and their mentors in terms of perceived patient satisfaction, suggesting patient perceived parity in care. Originality/value: Patient satisfaction was used innovatively to IDGs as an indicator of dental workforce programme effectiveness.